Aspectos biomédicos de cuatro casos de mordedura de serpiente por Lachesis muta (Ophidia: Viperidae) en Costa Rica - Bolaños, Róger (1982)
Three out of four cases of snake bite by Lachesis muta stenophrys (Bushmaster) in Costa Rica were fatal and one recovered after a long period of hospitalization. Initial symptoms were similar to those of bothropic envenomation: intense pain, nausea, vomiting, sweating, and excitability, but differing in the magnitude of a tremendous edema and in the absence of intensive bleeding and phlyctenae. We found important alterations in arterial blood pressure and in the activity and concentration of coagulation factors. All patients showed infections, and necrosis was found in at least three of them.